Downregulation of miR-760 Causes Human Intervertebral Disc Degeneration by Targeting the MyD88/Nuclear Factor-Kappa B Signaling Pathway - Cui, Xueliang; Li, Yanan; Bao, Junping; Wang, Kun; Wu, Xiaotao (Frontiers in Bioengineering and Biotechnology, 2022)
Dysregulation of microRNAs (miRNAs) plays a critical role in the development of intervertebral disc degeneration (IDD). In this study, we present evidence from in vitro and in vivo research to elucidate the mechanism underlying the role of miR-760 in IDD. miRNA microarray and quantitative reverse transcription-polymerase chain reaction were used to determine the miRNA profiles in patients with IDD. Functional analysis was performed to evaluate the role of miR-760 in the pathogenesis of IDD. Luciferase reporter and western blotting assays were used to confirm the miRNA targets. The expression of miR-760 was significantly decreased in degenerative nucleus pulposus (NP) cells and negatively correlated with disc degeneration grade. Functional assays demonstrated that miR-760 delivery significantly increased NP cell proliferation and promoted the expression of collagen II and aggrecan. Moreover, MyD88 was identified as a target gene of miR-760. miR-760 effectively suppressed MyD88 expression by interacting with the 3′-untranslated region, which was abolished by miR-760 binding site mutations. An in vivo experiment using an IDD mouse model showed that the upregulation of miR-760 could effectively suspend IDD. Therefore, miR-760 was found to play an important role in IDD and can be used as a promising therapeutic target for the treatment of patients with IDD.